Evaluasi Program Kelas Tahfizh Al-Qur’an dengan Model CIPP di Pondok Pesantren Tahfidz Muhammadiyah Al Fattah Malang - Najah, Aninda Tri Safinatun (Jurnal Evaluasi Pendidikan, 2024)
This research aims to evaluate the Qur'an memorization (Tahfizh) program at Pondok Pesantren Tahfidz Muhammadiyah Al Fattah Ngantang, Malang Regency, using the CIPP model (Context, Input, Process, Product). With the increasing number of pesantren (Islamic boarding schools) in Indonesia and the growing public interest in Tahfizh Qur'an programs, this research is relevant to review the effectiveness and sustainability of such programs. This study employs a qualitative approach by collecting data through interviews, observations, and document reviews. The data is then analyzed through data collection, data condensation, data presentation, and conclusion drawing. The results of this study indicate that the program overall achieves good outcomes. The context evaluation shows alignment between the program’s vision and mission and the institution’s guidelines, but there is a gap between the memorization targets and actual achievements. The input evaluation highlights the need for improvement in recruiting teachers and paying more attention to the students' memorization abilities. The process evaluation indicates that the schedule, teaching methods, and student motivation are well-organized. The product evaluation reveals that memorization achievements are still below the set standards. Therefore, this research emphasizes the importance of enhancing various aspects of the program to improve the quality and sustainability of Qur'an memorization in the future.